Book Review: Psychology of young people's social activity. Under the editorship of Rail Munirovich Shamionov. Moscow, Publishing house "Pero", 2020. 200 pages. 1,9 Mb [Electronic publication] - Alfiya R. Vagapova (Saratov State University, 2021)
It is an issue of great importance and necessity to study phenomenology of modern people's social activity within the context of perceiving it as a source of transformation of oneself and of society as a whole. Changes in certain forms of manifestation of social activity, as well as the locus of its orientation are conditioned by the interaction between many factors pertaining to multi-level order, which are integrated into the dynamic regulatory-functional system, reveal peculiarities of social changes, and, at the same time, reflect the general socio-historical context. The monograph written by a group of authors (R. M. Shamionov, M. V. Grigoryeva, I. V. Arendachuk, E. E. Bocharova, N. V. Usova, M. A. Klenova, A. A. Sharov, A. I. Zagranichny) presents the results of theoretical and empirical studies of the phenomenology, mechanisms and factors of young people's social activity according to provisions of the system-diachronic approach, which is being actively developed by Professor R. M. Shamionov's scientific school. Varied empirical material helps to establish some facts that indicate contradictory trends of functional manifestation in the development and limitations of certain social activity forms in various life spheres, depending on the social and age status of an individual, conditions and stages of socialization, as well as the context of real and virtual environment. The team of authors made an attempt to develop and validate the tool for evaluating a person's adherence to various forms of social activity (R. M. Shamionov, I. V. Arendachuk, E. E. Bocharova, et. al.) and its components (R. M. Shamionov, M. V. Grigoryeva); to adapt and validate the questionnaire published in the English language called CYBA (Cyber-aggression Questionnaire for Adolescents, D. Álvarez-García, A. Barreiro-Collazo, J. C. Núñez, A. Dobarro) on the Russian-speaking sample (A. A. Sharov), which allowed to record destructive practices of social activity, which were implemented in the virtual environment. The team of authors would like to express hope that the monograph can serve as a tool to clarify some of the aspects of social activity and social behavior of modern young people and can be useful for students and graduate students, whose academic work is related to young people's social activity.